2015
DOI: 10.3322/caac.21288
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and lesbian, gay, bisexual, transgender/transsexual, and queer/questioning (LGBTQ) populations

Abstract: This article provides an overview of the current literature on seven cancer sites that may disproportionately affect lesbian, gay, bisexual, transgender/transsexual, and queer/questioning (LGBTQ) populations. For each cancer site we present and discuss the descriptive statistics, primary prevention, secondary prevention and preclinical disease, tertiary prevention and late stage disease, and clinical implications. Finally, an overview of psychosocial factors related to cancer survivorship is offered as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
308
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 369 publications
(318 citation statements)
references
References 142 publications
(183 reference statements)
5
308
0
5
Order By: Relevance
“…Whilst identity and behaviour are overlapping categories, they must be distinguished in future research. An important implication is that sexual orientation should be routinely recorded as part of data collection in cohort studies, alongside medical records, to allow more large‐scale interpretation of disease patterns (and potential confounders) as previous authors have also concluded 28, 50. More work is required in developing countries, although matters such as routine recording may be problematic due to stigma or illegality of homosexuality.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst identity and behaviour are overlapping categories, they must be distinguished in future research. An important implication is that sexual orientation should be routinely recorded as part of data collection in cohort studies, alongside medical records, to allow more large‐scale interpretation of disease patterns (and potential confounders) as previous authors have also concluded 28, 50. More work is required in developing countries, although matters such as routine recording may be problematic due to stigma or illegality of homosexuality.…”
Section: Resultsmentioning
confidence: 99%
“…Human immunodeficiency virus infections are common among transgender people, particularly transwomen who have some of the highest laboratory-confirmed prevalence estimates in the world (29). For all of the above reasons, HPV-related cancers are expected to occur more frequently in transgender people than in the general population (30).…”
Section: Human Papillomavirus Infectionsmentioning
confidence: 99%
“…This inequality is evident in terms of access to the healthcare system and use of preventive health services [3,4]. As such, patients who identify as lesbian, gay, bisexual or transgender (LGBT) are at an increased risk for cancer, mental health disorders, substance abuse, and sexually transmitted infections [2,5,6]. Data shows that LGBT individuals receive poorer healthcare and often report a considerable degree of discrimination by medical students and practicing physicians.…”
Section: Introductionmentioning
confidence: 99%